Higher Education in Post-war Great Britain - Stewart, W. author. aut Link
XVIII, 362 p.
Keywords: This book is concerned with historical growth and change in higher education in Britain, as well as with the economic, social, cultural and political context in which these have taken place. The work examines polytechnics and the growth of institutes of higher education.